Legendrian normally flat submanifols of S-space forms - Mahi, F.; Belkhelfa, M. (Carpathian Mathematical Publications, 2020)
In the present study, we consider a Legendrian normally flat submanifold M of (2n+s)-dimensional S-space form M^2n+s(c) of constant φ-sectional curvature c. We have shown that if M is pseudo-parallel then M is semi-parallel or totally geodesic. We also prove that if M is Ricci generalized pseudo-parallel, then either it is minimal or L=1n-1, when c eq -3s.